OBSERVED COSMIC EVOLUTION OF GALAXY STELLAR MASS AND DARK MATTER HALO MASS - Zaidi, Kumail (Tufts University Tisch Library, 2025)
Thesis (Ph.D.)--Tufts University, 2025.; Submitted to the Dept. of Physics.; Advisor: Danilo Marchesini.; Committee: Anna Sajina, David Martin, Hugh Gallagher, and Kyoung-Soo Lee.; Keyword: Astrophysics.